Systematic Reviews of Research on Online Learning: An Introductory Look and Review - Martin, Florence; Dennen, Vanessa P.; Bonk, Curtis J. (Online Learning, 2023)
In this introduction to the special issue on systematic reviews of research on online learning, we introduce the need for systematic reviews on online learning. Utilizing a three-tier lens focusing on systems, pedagogical, and people levels, we have selected nine articles for this issue. At the systems level, there are two articles that focus on research trends during COVID-19, and features of high-quality online learning. At the pedagogical level, five articles were included that address online learner collaboration, help-seeking strategies, intersubjectivity, invisible participation, and online assessment. Finally, at the people level, there are two articles. The first focuses on online learning for minoritized and first-generation students. The second examines moderators in asynchronous online discussions. This introductory article provides a short summary of the nine articles and concludes with implications for practitioners and researchers on using and conducting systematic reviews on various topics in online learning.